PROCEDURE AND DOCUMENTS UNDER ARTICLES III AND IV OF NEW YORK CONVENTION ON RECOGNITION AND ENFORCEMENT OF ARBITRAL AWARDS: COMPARATIVE PRACTICE OF LATVIA AND GEORGIA - Tkemaladze, Sophie; Kacevska, Inga (European Scientific Journal, ESJ, 2014)
The publication aims to inform foreign legal professionals of the procedural steps and hurdles that they may face when seeking recognition and enforcement of foreign arbitral awards in Latvia and Georgia. It is also hoped that the article will facilitate uniform interpretation and application of 1958 New York Convention on Recognition and Enforcement of Arbitral Awards in Latvia and Georgia. With comparative analyses of case law regarding Article IV of Convention the authors indicate the inaccuracies made by the judges in the respective jurisdictions when recognizing and enforcing foreign arbitral awards and suggest how to comply with the spirit of New York Convention.